小児に生じた舌下オトガイ下型類皮囊胞の1例 - 飯田, 一規; 牧田, 浩樹; 加藤, 恵三; 柴田, 敏之; 阿部, 幸二郎; 畠山, 大二郎 (日本口腔外科学会雑誌, 2019)
Dermoid cysts in head and neck region are relatively rare. We report the case of a sublingual and submental type of dermoid cyst arising in an infant. A 5-year-old boy was referred to our department by his pediatrician because of a swelling in the submental region. MRI examination revealed a T1-low and T2-high cystic lesion in the submental and sublingual regions. The lesion penetrated the mylohyoid muscle. The cystic lesion was removed surgically with the patient under general anesthesia. Histopathologically, the cyst wall was lined with stratified squamous epithelium and contained skin appendages such as hair follicles and sebaceous and sweat glands. Histopathological diagnosis of a dermoid cyst was made. The postoperative course was uneventful.